Does Inflation Contribute to Economic Growth: The Case of CEMAC (Central African Economic and Monetary Community) - Mbon issie, Franchel (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
This paper focuses on the influence of inflation on economic growth to determine the extent to which the fight against inflation can contribute to the economic growth of a country or a regional zone such as CEMAC. We identify the effects of inflation on the CEMAC zone and use a multiple linear regression model to test the relationship between the two economic quantities: inflation and economic growth. We mainly used Stata 13 software to obtain the results and a sample of panel data, including six CEMAC member states, namely Congo, Cameroon, Gabon, Equatorial Guinea, Central African Republic, and Chad, from 2000 to 2018. The results were found to show a positive relationship between inflation and economic growth. These results indicate that the coefficients of the explanatory variables have the expected signs. However, other coefficients, up to 10%, are insignificant, notably GDP growth and consumer price inflation. The estimated values of all variables are in %, so we can say that if consumer price inflation increases by 10%, GDP growth will decrease by 10%. Then the value of GDP deflator inflation is positive, so if GDP deflator inflation increases by 1%, GDP will decrease by 0.11%. Its probability value is insignificant, and the money supply has a statistically insignificant effect on GDP growth. Finally, the results of the descriptive analysis show that GDP, consumer price inflation, the inflation deflator, the money supply, and foreign direct investment move in the same direction and the regression shows that there is a positive and significant link between the degree of openness to inflation and economic growth in the CEMAC zone. The econometric analysis allowed us to show that price increases (inflation) have a significant influence on growth.